1966
DOI: 10.1084/jem.124.4.753
|View full text |Cite
|
Sign up to set email alerts
|

Antigens of Leukemias Induced by Naturally Occurring Murine Leukemia Virus: Their Relation to the Antigens of Gross Virus and Other Murine Leukemia Viruses

Abstract: Leukemias can be induced in W/Fu inbred rats by neonatal inoculation of normal thymus cells of C58 mice. These leukemias are not transplantable to C58 mice or to adult W/Fu rats, but they can be kept in passage in W/Fu rats aged 0 to 7 days. Adult W/Fu rats inoculated repeatedly with these isogenic leukemias produce cytotoxic and precipitating antibodies. These antisera are of particular value in the analysis of the antigens of leukemia cells and of leukemia viruses because their mode of preparation precludes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
104
0

Year Published

1967
1967
1999
1999

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 255 publications
(111 citation statements)
references
References 10 publications
7
104
0
Order By: Relevance
“…antibodies (Geering, Old and Boyse, 1966), there is evidence that immune mouse lymphocytes recognize the antigen. Thus, p30 inhibits cell mediated cytotoxicity towards MLV target cells (Gorczynski and Knight, 1975a) and can stimnulate blast transformation by MSV immune lymphocytes (Knight and Gorczynski, 1975).…”
mentioning
confidence: 99%
“…antibodies (Geering, Old and Boyse, 1966), there is evidence that immune mouse lymphocytes recognize the antigen. Thus, p30 inhibits cell mediated cytotoxicity towards MLV target cells (Gorczynski and Knight, 1975a) and can stimnulate blast transformation by MSV immune lymphocytes (Knight and Gorczynski, 1975).…”
mentioning
confidence: 99%
“…'An antigen common to murine C-type RNA tumour viruses has been demonstrated by various serological techniques, including immunodiffusion (Geering, Old and Boyse, 1966) complement fixation (Hartley et al, 1965) and immunofluorescence (Lejneva and Abelev, 1970) and has been shown to be an internal component of the virus particle (Schafer et al, 1969). For the detection of this antigen, termed the species or group specific (gs) antigen (Gilden and Oroszlan, 1971), sera were raised in heterologous hosts bearing neoplasms induced by the murine agents or by immunization with disrupted virus particles.…”
Section: Discussionmentioning
confidence: 99%
“…Animals and tumours.-The Gross virusinduced lymphoma (C58NT)D (Geering et al, 1966) was maintained in ascitic form by weekly transplantation in weanling syngeneic W/Fu/Ico rats. The G-MuLV-induced lymphoma ESG2 (Old et al, 1965), R-MuLVinduced lymphoma RBL5 (McCoy et al, 1967), Graffi-virus (Gi-MuLV)-induced lymphoma GiL4 (Levy et al, 1968) and benzo(a)-pyrene-induced lymphoma EL4 (Gorer, 1950) were maintained in syngeneic C57BL/6/Ico mice.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, lymphomas induced by the Gross murine leukaemia virus (G-MuLV) express the Gross cell surface antigen (GCSA) which is specific for this MuLV and is not expressed on lymphomas induced by MuLV of the Friend-MoloneyRauscher (FMR) group (Old et al, 1965;Geering et al, 1966). The specificity of GCSA expression can however be questioned in studies of in vitro cultured cells, since in vitro infection of fibroblasts by FMR-MuLV can result in GCSA expression (O'Donnel & Stockert, 1976).…”
Section: Retrovirus-ind Uced) Tumours Bearmentioning
confidence: 99%
See 1 more Smart Citation